Eradication of Enterococcus faecalis by phage therapy in chronic bacterial prostatitis--case report - Letkiewicz, S; Miedzybrodzki, R; Fortuna, W; Weber-Dabrowska, B; Górski, A (Folia microbiologica, 2009)
The treatment of three patients suffering from chronic bacterial prostatitis who were qualified for an experimental phage therapy protocol managed at the Phage Therapy Unit in Wrocław is described. They had previously been treated unsuccessfully with long-term targeted antibiotics, autovaccines, and laser biostimulation. Rectal application of phage lysates targeted against Enterococcus faecalis cultured from the prostatic fluid gave encouraging results regarding bacterial eradication, abatement of clinical symptoms of prostatitis, and lack of early disease recurrence.
Keywords: grampozitivní bakteriální infekce; prostatitida; Enterococcus faecalis; Adult; dospělí; Gram-Positive Bacterial Infections; Humans; bakteriofágy; mužské pohlaví; lidé; Bacteriophages; Male; biologická terapie; Prostatitis; Biological Therapy